Pengaruh Kekerasan Fisik dan Seksual terhadap Kesehatan Mental Anak: Pengaruh Kekerasan Fisik dan Seksual Terhadap Kesehatan Mental Anak - Himamie, Rushoyfah (Maliki Interdisciplinary Journal, 2024)
Cases of violence against children are often found in Indonesia. According to data from the Ministry of Women’s Empowerment and Child Protection, as many as 3,956 cases were verified as of January 1 2024. The aim of this research is to see whether there is a relationship between violence experienced by children, both physical and sexual violence, and their mental health. The research method used is literature study with various reference sources. The results of the research show that there is an influence between physical or sexual violence on children’s mental health conditions.